An Intranasal Virus-Like Particle Vaccine Broadly Protects Mice from Multiple Subtypes of Influenza A Virus - Louis M. Schwartzman (American Society for Microbiology, 2015)
ABSTRACT Influenza virus infections are a global public health problem, with a significant impact of morbidity and mortality from both annual epidemics and pandemics. The current strategy for preventing annual influenza is to develop a new vaccine each year against specific circulating virus strains. Because these vaccines are unlikely to protect against an antigenically divergent strain or a new pandemic virus with a novel hemagglutinin (HA) subtype, there is a critical need for vaccines that protect against all influenza A viruses, a so-called “universal” vaccine. Here we show that mice were broadly protected against challenge with a wide variety of lethal influenza A virus infections (94% aggregate survival following vaccination) with a virus-like particle (VLP) vaccine cocktail. The vaccine consisted of a mixture of VLPs individually displaying H1, H3, H5, or H7 HAs, and vaccinated mice showed significant protection following challenge with influenza viruses expressing 1918 H1, 1957 H2, and avian H5, H6, H7, H10, and H11 hemagglutinin subtypes. These experiments suggest a promising and practical strategy for developing a broadly protective “universal” influenza vaccine. IMPORTANCE The rapid and unpredictable nature of influenza A virus evolution requires new vaccines to be produced annually to match circulating strains. Human infections with influenza viruses derived from animals can cause outbreaks that may be associated with high mortality, and such strains may also adapt to humans to cause a future pandemic. Thus, there is a large public health need to create broadly protective, or “universal,” influenza vaccines that could prevent disease from a wide variety of human and animal influenza A viruses. In this study, a noninfectious virus-like particle (VLP) vaccine was shown to offer significant protection against a variety of influenza A viruses in mice, suggesting a practical strategy to develop a universal influenza vaccine.